A field study of entrepreneurial decision-making and moral imagination - McVea, John F. (Journal of Business Venturing, 2009)
How entrepreneurs make decisions under extreme uncertainty and ambiguity is central to explaining entrepreneurial success. However, because of their pioneering nature, these decisions also have significant ethical implications. While there has been an increasing focus on the unique approaches entrepreneurs take to decision-making, less attention has been paid to the inherent ethical dimension of making decisions under high uncertainty. This study applies the concept of moral imagination to the challenges of making entrepreneurial decisions under Knightian uncertainty. It examines the extent to which entrepreneurs use moral imagination to integrate the ethical dimensions of pioneering situations into their decision-making.